The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/md.0000000000017009
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil extracted from erythrina corallodendron L. leaves inhibits the proliferation, migration, and invasion of breast cancer cells

Abstract: Erythrina corallodendron L., a kind of landscape tree, has long been used as a traditional medicine. In this study, the composition of essential oil extracted from the leaves was analysed by GC-MS (gas chromatograph-mass spectrometer), with linalool identified as the main compound. Its cytotoxicity against MDA-MB-231, MCF-7 and HMLE cells was examined by MTT and cloning assays. Transwell and wound-healing assays were used to examine the inhibition of migration and invasion. Western blot, qRT-PCR and immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The results indicated a significant dose-dependent decrease in the cell migration index of MDA-MB-468 cells exposed to both EOs compared to the nontreated cells. The inhibitory effects on NO production detected in the study could be one of the mechanisms of antimigratory potential of the tested EOs, since numerous studies indicate that the reduction of nitric oxide levels can inhibit cell migration [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated a significant dose-dependent decrease in the cell migration index of MDA-MB-468 cells exposed to both EOs compared to the nontreated cells. The inhibitory effects on NO production detected in the study could be one of the mechanisms of antimigratory potential of the tested EOs, since numerous studies indicate that the reduction of nitric oxide levels can inhibit cell migration [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies reported anticancer effects of this phytochemical in vitro and in vivo. This action of linalool has been mainly attributed to its anti-proliferative and cytotoxic effects on different types of tumor cells through the generation of oxidative stress, induction of cell cycle arrest and suppression of the epithelial-mesenchymal transition (EMT) process [32][33][34][35][36]. In contrast, the effects of linalool on angiogenesis, which is essential for tumor growth and metastasis, remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that points to it being a possible good target for a new chemotherapeutic agent is that ECEO had greater cytotoxicity to breast cancer cells MDA-MB-231 and MCF7 than to normal human mammary epithelial cells (HMLEs). Although it was not as good as the positive drugs, it may qualify as an adjuvant drug [21].…”
Section: Induction Of Apoptosis In Breast Cancer Cells By Essential Oilsmentioning
confidence: 95%